2014
DOI: 10.18296/set.0331
|View full text |Cite
|
Sign up to set email alerts
|

Reo and mātauranga Māori revitalisation: Learning visions for the future

Abstract: Te reo and mātauranga Māori are linked to a distinctive Māori identity and ways of being in the world. With the majority of Māori students enrolled in English-medium schools, we face the national challenge of how to affirm and promote reo and mātauranga Māori as part of the “everyday” in educational and community life, now and in the future. This article illustrates how educators in English-medium settings can deliberately affirm, support, and promote reo and mātauranga Māori in their learning processes and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…They highlighted six principles that were important to Māori educational success: Treaty of Waitangi, Māori potential approach, identity, language and culture, ako (learning) and productive partnerships. These findings align closely with other published literature (Doherty, 2009; Duckworth et al, 2021; Hotere-Barnes et al, 2014; Macfarlane et al, 2014).…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…They highlighted six principles that were important to Māori educational success: Treaty of Waitangi, Māori potential approach, identity, language and culture, ako (learning) and productive partnerships. These findings align closely with other published literature (Doherty, 2009; Duckworth et al, 2021; Hotere-Barnes et al, 2014; Macfarlane et al, 2014).…”
Section: Introductionsupporting
confidence: 93%
“…The authors suggested that schools need to focus on connecting to place, promote whanaungatanga, take a multidisciplinary approach to teaching and learning, and to explore realistic gauges of success. The schools in this study display many of the characteristics described in the scenario by Hotere-Barnes et al (2014) such as a commitment to Te Ao Māori and mātauranga Māori in the school environment alongside being community and student-focused.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation